A genre-inspired investigation of establishing the territory in thesis introductions by Malaysian ESL writers - Siti Zaidah Zainuddin,; Azianura Hani Shaari, (Penerbit Universiti Kebangsaan Malaysia, 2021)
This study looks at how ESL writers establish their research territory in their introductory chapters within the Applied Linguistics discipline. Eight PhD theses from three public universities were identified and selected as sample. The theses were chosen based on four criteria. The two disciplines selected were social sciences and humanities. This is to make sure that the corpora are similar in terms of the variation of the textual patterns. The analysis was performed using Swales’ (1990) CARS model. This study employed a systematic analysis that balances the functional-semantic approach in the identification of moves and the constituent steps involved in a particular social event. The genre-based investigation reveals that even though the moves follow that of Swales’ (1990) CARS model, the steps are different. Apart from that, this study also finds that a step can also be realised by several sub-steps after utilising a functional-semantic analysis to coding. Based on the findings, some practical implications of the research, in the form of suggestions for teaching masters and doctoral candidates about the construction and use of rhetorical strategies, from Malaysian and international perspectives are presented.